2016
DOI: 10.3389/fpls.2016.01967
|View full text |Cite
|
Sign up to set email alerts
|

Varying Response of the Concentration and Yield of Soybean Seed Mineral Elements, Carbohydrates, Organic Acids, Amino Acids, Protein, and Oil to Phosphorus Starvation and CO2 Enrichment

Abstract: A detailed investigation of the concentration (e.g., mg g-1 seed) and total yield (e.g., g plant-1) of seed mineral elements and metabolic profile under phosphorus (P) starvation at ambient (aCO2) and elevated carbon dioxide (eCO2) in soybean is limited. Soybean plants were grown in a controlled environment at either sufficient (0.50 mM P, control) or deficient (0.10 and 0.01 mM, P-stress) levels of P under aCO2 and eCO2 (400 and 800 μmol mol-1, respectively). Both the concentration and yield of 36 out of 38 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
43
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 51 publications
13
43
1
Order By: Relevance
“…The exceptions were the traits whose heritability estimates were <0.50, including seed contents of glucose, fructose, valine, and proline. Grieshop and Fahey (2001) and Karr-Lilienthal et al (2005) suggested that differences in temperature among studied environments may contribute to variation in amino acid content, and Singh et al (2016) stated that the free amino acid increased when there was a deficit of phosphate, and the seed amino acid decreased under elevated CO 2 conditions. The heritability estimates for amino acids on an entrymean basis for Set 2 were relatively high, with a range of 0.30 to 0.84 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exceptions were the traits whose heritability estimates were <0.50, including seed contents of glucose, fructose, valine, and proline. Grieshop and Fahey (2001) and Karr-Lilienthal et al (2005) suggested that differences in temperature among studied environments may contribute to variation in amino acid content, and Singh et al (2016) stated that the free amino acid increased when there was a deficit of phosphate, and the seed amino acid decreased under elevated CO 2 conditions. The heritability estimates for amino acids on an entrymean basis for Set 2 were relatively high, with a range of 0.30 to 0.84 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The highest average content of 6 of the 12 amino acids was observed in 15NOV. Grieshop and Fahey (2001) and Karr-Lilienthal et al (2005) suggested that differences in temperature among studied environments may contribute to variation in amino acid content, and Singh et al (2016) stated that the free amino acid increased when there was a deficit of phosphate, and the seed amino acid decreased under elevated CO 2 conditions. To our knowledge, the results of this study are some of the first published and publicly available amino acid data sets in wild soybean seed grown across multiple replications and environments.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, dilution by enhanced carbohydrate production at eCO 2 or dilution by increased seed production could contribute to the reduced mineral concentrations observed. Dilution by enhanced carbohydrate production cannot explain all of the effects of eCO 2 (McGrath and Lobell, ), but the impact of changes in seed yield on the content of minerals on a plant basis (Singh et al ., ) has not been broadly considered. However, it is reasonable to assume that if a micronutrient is obtained in controlled or limited amounts it would be diluted when distributed amongst a greater number of seeds produced at eCO 2 , such that the concentration would decrease while the mineral seed content per plant would not change.…”
Section: Introductionmentioning
confidence: 99%
“…However, the response of seed metabolic profiles under different K fertilization regimes have been found vary under field conditions [12] [13] [14], especially due to the interactions with other existing factors such as temperature and soil moisture contents in fields [2] [12] [13] [14]. In the controlled environment conditions, we have reported that the deficiency of a given mineral nutrients including K and phosphorus (P) leads to the alteration in the concentration of several other minerals elements and seed constituents in plant and seed tissues [10] [11] [27]. In the previous report, we found that under K deficiency the depressed soybean productivity was primarily associated with the decreased growth traits such as plant size and total leaf area than the photosynthetic processes across CO 2 levels [11].…”
Section: Introductionmentioning
confidence: 99%